The Cultural Economy of Survival: The Mi’kmaq of Cape Breton in the Mid-19th Century - Parnaby, Andrew (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2008)
Abstract By the mid-th century, the Mi’kmaq of Cape Breton Island, much like the Mi’kmaq on the Nova Scotia mainland, were nearly destitute. The outcome of over two centuries of political, economic, and cultural interaction with Europeans, this condition was exacerbated by the massive influx of Scottish settlers to the island after the end of the Napoleonic Wars – nearly 30,000 between 1815 and 1838. With their lands occupied and access to customary hunting and fishing grounds severely limited, the island’s Mi’kmaw population – estimated to be about 500 in 1847 – adopted numerous economic initiatives to stay alive: they pursued agriculture and wage labour, mobilized older skills toward diﬀerent occupational niches, and maintained, at least to some extent, customary rounds of seasonal resource procurement. This essay examines this evolving pattern of occupational pluralism, and highlights how customary norms, codes, and behaviours provided part of the logic through which the island’s Mi’kmaw people made decisions about what to do, economically, to survive. Mid-19th century Cape Breton was a contested place as the forces of immigration and settlement exerted new pressures on Mi’kmaw life. This paper is about that changing context and how the island’s indigenous people sought to understand it, negotiate its pressures and possibilities, and blunt its negative eﬀects.